Sticks, Stones, and Molotov Cocktails: Unarmed Collective Violence and Democratization. (31st May 2018) - Kadivar, Mohammad Ali; Ketchley, Neil
The literature on civil resistance finds that nonviolent campaigns are more likely to succeed than violent insurgencies. A parallel literature on democratization poses mass mobilization as exogenous to political liberalization. Contributing to both literatures, we propose the category of unarmed collective violence to capture an empirically recurring form of unruly collective action used by civilians and then use a mixed methods research design to examine its impact on democratization. An event history analysis finds that riots are positively associated with political liberalization in 103 nondemocracies from 1990 to 2004. Attacks by civilians on police stations during the January 25 Egyptian Revolution illustrate one way in which unarmed collective violence can bring about a democratic breakthrough. A qualitative examination of all 80 democratic transitions held between 1980 and 2010 also reveals the salience of unarmed collective violence by civilian forces. These findings contribute to research on the dynamics of contentious democratization and suggest that remaining unarmed may be more consequential for a democracy campaign than adhering to nonviolence.